Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Team Games Tournament (TGT) pada Pembelajaran Pendidikan Pancasila di Kelas IV SDN 11 Ampang Kota Padang - Putri, Rada Nelsa; Indrawati, Tin; Adrias, Adrias; Ladiva, Hasmai Bungsu; Zuryanty, Zuryanty (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the improvement of student learning outcomes using the Team Games Tournament (TGT) model in Pancasila Education learning in class IV SDN 11 Ampang, Padang City. This study is a Classroom Action Research (CAR) using a qualitative and quantitative approach which is carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects in this study were teachers and students of class IV SDN 11 Ampang totaling 15 people in the January-June semester of the 2024/2025 academic year. The research data are in the form of observations of teaching modules, observations of teacher and student activities, and student learning outcomes using the Team Games Tournament (TGT) model. Data collection techniques are in the form of observation analysis, tests and non-tests. The results of observations of planning cycle I were 88.27% (B), increasing in cycle II to 95.31% (SB). The results of observations of teacher aspects in cycle I were 85.71% (B), increasing in cycle II to 96.42% (SB). The results of observations of student aspects in cycle I were 82.14% (B), increasing in cycle II to 96.42% (SB). Student learning outcomes in cycle I were 78.30% (C), increasing in cycle II to 87.88% (B). Research shows that the Team Games Tournament (TGT) model can improve student learning outcomes in Civic Education learning in the fourth grade of SDN 11 Ampang Kota Padang.